The Cambridge world history of violence - Dwyer, Philip; Damousi, Joy (Cambridge University Press, 2020)
Volume 1. The prehistoric and ancient worlds -- Volume 2. 500-1500 CE -- Volume 3. 1500-1800 CE -- Volume 4. 1800 to the present